Growth Hormone Increases Bone Toughness and Decreases Muscle Inflammation in Glucocorticoid‐Treated Mdx Mice, Model of Duchenne Muscular Dystrophy. (12th June 2019) - Yoon, Sung‐Hee; Grynpas, Marc D; Mitchell, Jane
ABSTRACT: The absence of functional dystrophin with mutations of the dystrophin‐encoding gene in Duchenne muscular dystrophy (DMD) results in muscle inflammation and degeneration, as well as bone fragility. Long‐term glucocorticoid therapy delays the muscular disease progression but suppresses growth hormone secretion, resulting in short stature and further deleterious effects on bone strength. This study evaluated the therapeutic potential of daily growth hormone therapy in growing mdx mice as a model of DMD. Growth hormone treatment on its own or in combination with glucocorticoids significantly improved muscle histology and function and decreased markers of inflammation in mdx mice. Glucocorticoid treatment thinned cortical bone and decreased bone strength and toughness. Despite the minimal effects of growth hormone on bone microarchitecture, it significantly improved biomechanical properties of femurs and vertebrae, even in the presence of glucocorticoid treatment. Together these studies suggest that the use of growth hormone in DMD should be considered for improvements to muscle and bone health. © 2019 American Society for Bone and Mineral Research.